PRINCIPLE ROCK TYPES FOR RADIOACTIVE WASTE REPOSITORIES - Sibila Borojević Šostarić; Franz Neubauer (Rudarsko-geološko-naftni Zbornik, 2012)
Underground geological storage of high- and intermediate/low radioactive waste is aimed to represent a barrier between the surface environment and potentially hazardous radioactive elements. Permeability, behavior against external stresses, chemical reacatibility and absorption are the key geological parameters for the geological storage of radioactive waste. Three principal rock types were discussed and applied to the Dinarides: (1) evaporites in general, (2) shale, and (3) crystalline basement rocks. (1) Within the Dinarides, evaporite formations are located within the central part of a Carbonate platform and are inappropriate for storage. Offshore evaporites are located within diapiric structures of the central and southern part of the Adriatic Sea and are covered by thick Mesozoic to Cenozoic clastic sediment. Under very specific circumstances they can be considered as potential site locations for further investigation for the storage of low/intermediate level radioactive wast e. (2) Thick flysch type formation of shale to phyllite rocks are exposed at the basement units of the Petrova and Trgovska gora regions whereas (3) crystalline magmatic to metamorphic basement is exposed at the Moslavačka Gora and Slavonian Mts. regions. For high-level radioactive waste, basement phyllites and granites may represent the only realistic potential option in the NW Dinarides.